2013
DOI: 10.1371/journal.pone.0073057
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Risk for Bipolar Disorders: A Nationwide Population-Based Study

Abstract: BackgroundThyroid disorders have long been associated with psychiatric illness, often with symptoms suggestive of mood disorders. The most common clinical features associated with hyperthyroidism are anxiety and depression. The risk of bipolar disorders, especially bipolar mania, among patients with thyroid disorders has not been well characterized.ObjectiveWe explored the relationship of hyperthyroidism and the subsequent development of bipolar disorders, and examined the risk factors for bipolar disorders in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
0
31
0
3
Order By: Relevance
“…Previous study found that hypothalamic-pituitary-thyroid (HPT) axis abnormalities play an important role in the pathophysiology and treatment of BD [18]. Researchers also found that hyperthyroidism may increase the risk of developing BD [19]. Higher tri-iodothyronine (T3) hormone was found in BD patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study found that hypothalamic-pituitary-thyroid (HPT) axis abnormalities play an important role in the pathophysiology and treatment of BD [18]. Researchers also found that hyperthyroidism may increase the risk of developing BD [19]. Higher tri-iodothyronine (T3) hormone was found in BD patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing recognition that thyroid dysfunction is associated with neurological and psychiatric disease, including neurodevelopmental disorders such as intellectual disability and autism spectrum disorder (ASD), focal and generalised neurological abnormalities, as well as psychiatric manifestations such as psychosis, panic attacks, anxiety disorders, bipolar disorder, depression and schizophrenia . In addition, normal thyroid function is essential for normal cognition .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile a study in Poland showed that the prevalence of thyroid dysfunction was higher in mood disorders [2]. Hu LY et al [3] explored the relationship of hyperthyroidism and the subsequent development of bipolar disorders and they found that patients with hyperthyroidism were more likely to develop bipolar disorder [3]. These studies demonstrate the importance of thyroid function in the development of various disorders.…”
Section: Introductionmentioning
confidence: 99%